Oxidative renal damage in pyelonephritic rats is ameliorated by montelukast, a selective leukotriene CysLT1 receptor antagonist - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (ELSEVIER SCIENCE BV, 2007)
Urinary tract infections may induce severe inflammation, transient impairment in renal function and scar formation, ranging in severity from acute symptomatic pyelonephritis to chronic pyelonephritis, which have a potential to lead to renal failure and death. The present study aimed to investigate the possible protective effect of montelukast, a selective antagonist of cysteinyl leukotriene receptor I (leukotriene CysLT1), against Escherichia coli-induced oxidative injury and scarring in renal tissue. Wistar rats were injected 0.1 ml of E. coli (ATCC 25922 10(10) cfu/ml) or saline into left renal medullae. Six rats were assigned as the sham group and were given 0.1 ml 0.9% NaCl. Pyelonephritic rats were treated with either saline or montelukast immediately after surgery and at daily intervals. Twenty-four hours or one week after E. coli injection, rats were decapitated and the kidney samples were taken for histological examination or determination of renal malondialdehyde, glutathione (GSH) levels, myeloperoxidase (MPO) activity, and collagen contents. Formation of reactive oxygen species in renal tissue samples was monitored by using chemiluminescence technique with luminol and lucigenin probes. Creatinine, blood urea nitrogen and lactate dehydrogenase (LDH) activity were measured in the serum samples. E. coli inoculation caused significant increases in malondialdehyde level, MPO activity, chemiluminescence levels and collagen content, while GSH level was decreased in the renal tissues (p < 0.05-0.001). On the other hand, serum TNF-alpha, LDH, blood urea nitrogen and serum creatinine levels were elevated in the pyelonephritic rats as compared to control group. Leukotriene CysLT1 receptor antagonist montelukast reversed all these biochemical indices, as well as histopathological alterations, that were induced by acute pyelonephritis. It seems likely that montelukast protects kidney tissue by inhibiting neutrophil infiltration, balancing oxidant-antioxidant status, and regulating the generation of inflammatory mediators suggesting a future role for leukotriene CysLT1 receptor antagonists in the treatment of pyclonephritis. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Escherichia coli; montelukast; glutathione; lipid peroxidation; myeloperoxidase activity; TNF-alpha; ESCHERICHIA-COLI PYELONEPHRITIS; HEMODIALYSIS-PATIENTS; BLOCKER MONTELUKAST; REPERFUSION INJURY; ACUTE SUPPURATION; IN-VIVO; GLOMERULONEPHRITIS; SUPPRESSION; MECHANISMS; INHIBITION